THE EFFECT OF BRAND ENGAGEMENT, BRAND IMAGE, AND BRAND AWARENESS ON CUSTOMER LOYALTY - Wilda Khoirunnisa; R.A. Marlien (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
Telkomsel is one of the best providers in Indonesia with loyal customers. Business competition is a challenge that must be faced by Telkomsel companies. Innovations to improve the quality of products and services are continuously carried out. This study aims to examine and analyze the effect of Brand Engagement, Brand Image, and Brand Awareness on customer loyalty. The respondents used in this study are Telkomsel customers who have or often interacted to provide comments on Telkomsel's Instagram and Facebook. Purposive sampling method was used for the sampling technique and obtained 133 respondents. The data analysis method used multiple regression.This study resulted in the findings that the variables Brand Engagement, Brand Image, and Brand Awareness have a positive and significant effect on customer loyalty.